Growing the urban forest: tree performance in response to biotic and abiotic land management. Issue 5 (29th May 2015) - Oldfield, Emily E.; Felson, Alexander J.; Auyeung, D. S. Novem; Crowther, Thomas W.; Sonti, Nancy F.; Harada, Yoshiki; Maynard, Daniel S.; Sokol, Noah W.; Ashton, Mark S.; Warren, Robert J.; Hallett, Richard A.; Bradford, Mark A.
Abstract : Forests are vital components of the urban landscape because they provide ecosystem services such as carbon sequestration, storm‐water mitigation, and air‐quality improvement. To enhance these services, cities are investing in programs to create urban forests. A major unknown, however, is whether planted trees will grow into the mature, closed‐canopied forest on which ecosystem service provision depends. We assessed the influence of biotic and abiotic land management on planted tree performance as part of urban forest restoration in New York City, U.S.A. Biotic treatments were designed to improve tree growth, with the expectation that higher tree species composition (six vs. two) and greater stand complexity (with shrubs vs. without) would facilitate tree performance. Similarly, the abiotic treatment (compost amendment vs. without) was expected to increase tree performance by improving soil conditions. Growth and survival was measured for approximately 1, 300 native saplings across three growing seasons. The biotic and abiotic treatments significantly improved tree performance, where shrub presence increased tree height for five of the six tree species, and compost increased basal area and stem volume of all species. Species‐specific responses, however, highlighted the difficulty of achieving rapid growth with limited mortality. Pioneer species had the highest growth in stem volume over 3 years (up to 3, 500%), but also the highest mortality (up to 40%). Mid‐successional species had lower mortality (<16%), but also the slowest growth in volume (approximately 500% in volume). Our results suggest that there will be trade‐offs between optimizing tree growth versus survival when implementing urban tree planting initiatives.